Rhodium-based composite catalyst for high alcohols as well as preparation method and application of rhodium-based composite catalyst

Through the alloying of Rh-based composite catalyst with Fe, Mn, K or Cs and acid-base dual-function treatment of acid-base support, the problem of poor selectivity and ease of inactivation in the reaction of high carbon alcohol by syngas is solved, and high selectivity and stability are achieved.

CN120268415AActive Publication Date: 2025-07-08BEIJING GAOXIN LIHUA TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510772075.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-11
Publication Date
2025-07-08
Estimated Expiration
2045-06-11

AI Technical Summary

Technical Problem

The existing rhodium-based catalysts have poor selectivity in the reaction to high carbon alcohol by syngas, are prone to sintering and inactivation, are costly, and are susceptible to impurities such as sulfur and chlorine.

Method used

Using Rh-based composite catalyst, an alloy is formed with Rh by introducing metals such as Fe, Mn, K or Cs and Rh, combining ZrO2 or H-ZSM-5 acid support, and amino silanization treatment is carried out to form an acid-base bifunctional catalyst, inhibiting excessive dissociation of CO, promoting C-C coupling, improving high-carbon alcohol selectivity and inhibiting sintering.

Benefits of technology

It improves the selectivity of high-carbon alcohol and the stability of the catalyst, reduces the risk of easy sintering and poisoning of the catalyst, and ensures the long-term stability and efficient operation of the catalyst.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention provides a rhodium-based composite catalyst for high alcohols as well as a preparation method and application of the rhodium-based composite catalyst, and relates to the technical field of catalysts. The rhodium-based composite catalyst for high alcohols comprises a first active metal, a second active metal and an amino silanized acidic carrier, the first active metal is Rh, the second active metal is one or more of Fe, Mn, K or Cs, and the acidic carrier is ZrO2 or H-ZSM-5. The problems that an existing rhodium-based catalyst is poor in high alcohol (C6 +) selectivity, prone to sintering and inactivation and high in cost are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalysts, and more specifically, to a rhodium-based composite catalyst for higher alcohols, a preparation method thereof, and an application thereof. Background Art

[0002] Higher alcohols (C6+ alcohols) are an important class of chemical raw materials with broad application prospects. For example, they are used in detergents, high-grade cosmetics and fragrances, high-grade emulsifiers and dispersants, plasticizers, and alcohol fuel additives. Currently, the preparation of higher alcohols is mainly obtained through processes such as petroleum cracking and olefin carbonylation. The direct synthesis of higher alcohols from syngas has the advantages of a short process flow, low energy consumption, etc., and can avoid dependence on petroleum resources. However, currently, the content of higher alcohols in the products obtained from the Fischer-Tropsch reaction of syngas is generally low, and the selectivities of by-products CH4 and CO2 are both > 30%. The main reason is the lack of a suitable catalyst.

[0003] Currently, several catalyst systems developed for the reaction of syngas to higher alcohols include modified Rh-based catalysts, Mo-based catalysts, modified methanol synthesis catalysts, and modified Fischer-Tropsch synthesis catalysts. Among them, rhodium-based catalysts have the following problems: ① Tend to generate methane and short-chain alkanes (such as C1-C4) rather than higher alcohols (C 6+ ), especially the side reactions intensify at high temperatures. The main reason is that the dissociation of CO on the Rh surface to generate C* species is prone to over-hydrogenation to form alkanes rather than inserting with CO to form alcohols, resulting in low selectivity. ② Rhodium nanoparticles are prone to aggregation (sintering) in high-temperature reactions (> 250 °C), resulting in a reduction in active sites, leading to easy sintering and deactivation. ③ Impurities such as sulfur (S) and chlorine (Cl - ) are prone to poisoning the rhodium active sites, resulting in catalyst deactivation. Summary of the Invention

[0004] In order to solve the above problems, the present invention provides a rhodium-based composite catalyst for higher alcohols, which solves the problems of poor selectivity of higher alcohols (C6+), easy sintering and deactivation, and high cost of existing rhodium-based catalysts.

[0005] In a first aspect of the present invention, there is provided a rhodium-based composite catalyst for higher alcohols, wherein the rhodium-based composite catalyst for higher alcohols comprises a first active metal, a second active metal, and an acidic support treated with aminosilane. The first active metal is Rh, the second active metal is one or more of Fe, Mn, K, or Cs, and the acidic support is ZrO2 or H-ZSM-5.

[0006] The rhodium-based composite catalyst for higher alcohols in this application forms an alloy by introducing metals such as Fe, Mn, K, or Cs to react with Rh, reducing costs. At the same time, Fe and Mn can weaken the dissociation ability of Rh for CO through the electron-donating effect, promoting the insertion of CO to generate higher alcohols (C6+). K or Cs can enhance the non-dissociative adsorption of CO and improve the selectivity of C6+ alcohols. Selecting an acidic support (ZrO2 or H-ZSM-5) can, on the one hand, promote the adsorption and dissociation of CO through Lewis acid sites, which can promote the insertion of CO and improve the selectivity of C6+ alcohols. On the other hand, the acidic surface forms a strong metal-support interaction with Rh, which can inhibit sintering and improve sulfur and chlorine tolerance. By using an acidic support treated with aminosilane in this invention, basic sites - amino groups are further introduced. This can further weaken the dissociative adsorption of Rh for H2 through the electron effect, reducing short-chain by-products such as methane. At the same time, the basic environment can further enhance the non-dissociative adsorption of CO and promote the coupling of CO with CH x to form higher alcohols (C6+) Optionally, by mass fraction, the first active metal is 0.5 wt% - 10 wt%, the second active metal is 0.5 wt% - 8 wt%, and the acidic support is 85 wt% - 98 wt%. Optionally, the first active metal can be 0.5 wt%, 1 wt%, 1.5 wt%, 2 wt%, 2.5 wt%, 3 wt%, 3.5 wt%, 4 wt%, 4.5 wt%, 5 wt%, 5.5 wt%, 6 wt%, 6.5 wt%, 7 wt%, 7.5 wt%, 8 wt%, 8.5 wt%, 9 wt%, 9.5 wt%, 10 wt% or any value and range therebetween.

[0007] Optionally, the second active metal can be 0.5 wt%, 1 wt%, 1.5 wt%, 2 wt%, 2.5 wt%, 3 wt%, 3.5 wt%, 4 wt%, 4.5 wt%, 5 wt%, 5.5 wt%, 6 wt%, 6.5 wt%, 7 wt%, 7.5 wt%, 8 wt% or any value and range therebetween.

[0008] Optionally, the acidic support treated with aminosilane can be 85 wt%, 86 wt%, 87 wt%, 88 wt%, 89 wt%, 90 wt%, 91 wt%, 92 wt%, 93 wt%, 94 wt%, 95 wt%, 96 wt%, 97 wt%, 98 wt% or any value and range therebetween.

[0009] In this application, Rh is a noble metal. A high loading amount (>10%) will significantly increase the cost and easily lead to particle agglomeration. A low loading may result in insufficient active sites. In this application, by adding a certain proportion of a second active metal to form an alloy with Rh, the electronic structure is adjusted to inhibit the excessive dissociation of CO and promote C-C coupling. ZrO2 and H-ZSM-5 are used as acidic carriers, and their acidity affects the adsorption of reactants and the stability of intermediates. By introducing a certain proportion of acid-treated carriers with aminosilane, the acid-base bifunction is achieved, forming a strong metal-support interaction with Rh, further improving the selectivity of higher alcohols, while sintering can be inhibited, sulfur and chlorine tolerance can be improved, and the stability of the catalyst can be ensured.

[0010] Optionally, the aminosilylation treatment of ZrO2 includes the following steps: a1: Wash ZrO2 with acid and then calcine it at 400 - 550 °C. For example, dilute nitric acid can be used for washing to remove surface impurities of ZrO2 and increase the hydroxyl density, thus increasing the active sites.

[0011] a2: Add the ZrO2 calcined in step a1 to a solution of 3-aminopropyltriethoxysilane and toluene, and carry out a reflux reaction at 75 - 85 °C; then wash to remove the unreacted 3-aminopropyltriethoxysilane.

[0012] a3: Calcine the ZrO2 after the reflux reaction in step a2 in an inert atmosphere at 250 - 350 °C to obtain aminosilylated ZrO2.

[0013] Optionally, the pore diameter of the aminosilylated ZrO2 is 5 - 10 nm, which is beneficial for the subsequent dispersion of Rh.

[0014] Optionally, the mass ratio of 3-aminopropyltriethoxysilane to ZrO2 is 5% - 10%, to avoid pore blockage caused by excessive APTES.

[0015] Optionally, the aminosilylation treatment of H-ZSM-5 includes the following steps: b1 Immerse H-ZSM-5 in an alkaline solution and treat it at 70 - 80 °C. For example, immerse H-ZSM-5 in a 0.1 - 0.5 M sodium hydroxide solution for treatment, and partially dissolve the silica-alumina framework to generate mesopores. Optionally, the pore diameter of H-ZSM-5 after alkali treatment is enlarged to 2 - 5 nm, facilitating the subsequent entry of 3-aminopropyltriethoxysilane into the pore interior.

[0016] b2 Acid-wash the H-ZSM-5 after alkali treatment in step b1, and then dry and calcine it in sequence to obtain activated H-ZSM-5; for example, the enlarged-pore H-ZSM-5 can be washed with 0.1 - 0.3 M dilute nitric acid to remove the residual alkali solution and increase the surface hydroxyl density.

[0017] b3 Immerse the activated H-ZSM-5 into a solution of 3-aminopropyltriethoxysilane and toluene, and carry out a reflux reaction at 75-85 °C to fully graft the silane. Then, dry it and perform heat treatment under an inert atmosphere to obtain the amino-silylated H-ZSM-5.

[0018] Optionally, the calcination temperature in step b2 is 450-550 °C.

[0019] Optionally, the heat treatment temperature under an inert atmosphere in step b3 is 140-160 °C.

[0020] Optionally, the mass ratio of 3-aminopropyltriethoxysilane to H-ZSM-5 is 5%-15%.

[0021] The second aspect of the present invention provides a preparation method of a rhodium-based composite catalyst for higher alcohols. The preparation method includes the following steps: (1) Weigh the corresponding soluble salts and acidic carriers respectively according to the proportions of the first active metal and the second active metal in the total mass of the catalyst. Mix the soluble salt of the first active metal with the first solvent to obtain the first solution; mix the soluble salt of the second active metal with the second solvent to obtain the second solution. Optionally, the first solvent can be dilute hydrochloric acid, and the second solvent can be deionized water or propanol. However, the present invention is not limited thereto.

[0022] (2) Immerse the first solution into the carrier, and after drying, perform reduction treatment at a certain temperature to obtain the acidic carrier loaded with the first active metal. (3) Immerse the second solution into the acidic carrier loaded with the first active metal, and after drying, perform calcination treatment to obtain the acidic carrier loaded with the second active metal. (4) Perform reduction treatment on the acidic carrier loaded with the second active metal at a certain temperature, and then sequentially perform passivation and calcination and qualification treatment to obtain the rhodium-based composite catalyst for higher alcohols.

[0023] Optionally, the soluble salt of the first active metal is one of rhodium chloride or rhodium nitrate.

[0024] Optionally, the soluble salt of the second active metal is one or more of ferric nitrate, ferrous sulfate, manganese nitrate, manganese sulfate, potassium nitrate, cesium nitrate, and cesium chloride.

[0025] Optionally, the reduction treatment temperature in step (2) is 250-300 °C. Optionally, the Rh particles <5 nm, and reducing Rh below 300 °C can inhibit particle agglomeration.

[0026] Optionally, the calcination temperature in step (3) is 350-450 °C.

[0027] Optionally, in step (4), the reduction treatment temperature is 300 - 350 °C, and the calcination and qualitative treatment temperature is 400 - 550 °C.

[0028] The third aspect of the present invention provides a use of a rhodium-based composite catalyst for higher alcohols in the direct preparation of higher alcohols from syngas.

[0029] Optionally, the catalyst is pre-reduced first, and the pre-reduced catalyst is used for the synthesis of higher alcohols from syngas. The reduction temperature is 300 - 400 °C, the reduction gas is hydrogen, CO, or a mixture of both, and the space velocity is 2000 - 8000 h -1 , and the reduction treatment time is 5 - 10 h.

[0030] Optionally, in the reaction of directly preparing higher alcohols from syngas, the molar ratio of H2 to CO in the syngas is 0.5 - 5, the reaction temperature is 200 - 400 °C, and the reaction space velocity is 3000 - 6000 h -1 , and the reaction pressure is 3 - 9 MPa.

[0031] Optionally, in the reaction of directly preparing higher alcohols from syngas, the reactor is one of a fixed-bed reactor, a fluidized-bed reactor, or a slurry-bed reactor, and its specific structure and form are not specifically limited in the present invention.

[0032] Compared with the prior art, the present invention achieves at least one of the following beneficial effects: (1) The rhodium-based composite catalyst for higher alcohols of the present invention solves the problems of poor selectivity of higher alcohols (C6+) in the existing rhodium-based catalysts, easy sintering and deactivation, and high cost.

[0033] (2) In the rhodium-based composite catalyst for higher alcohols of the present invention, by adding a certain proportion of a second active metal to form an alloy with Rh, the electronic structure is adjusted to inhibit the excessive dissociation of CO and promote C-C coupling. ZrO2 and H-ZSM-5 are used as acidic carriers, and their acidity affects the adsorption of reactants and the stability of intermediates. By introducing a certain proportion of acid carriers treated with aminopropyltriethoxysilane, the acid-base bifunction is realized, and a strong metal-support interaction is formed with Rh, further improving the selectivity of higher alcohols, and at the same time, sintering can be inhibited, the sulfur and chlorine tolerance can be improved, and the stability of the catalyst can be ensured.

[0034] (3) The rhodium-based composite catalyst for higher alcohols of the present invention uses 3-aminopropyltriethoxysilane to treat ZrO2 to realize the acid-base bifunction, laying a foundation for the subsequent formation of a strong metal-support interaction with Rh.

[0035] (4) The rhodium-based composite catalyst for higher alcohols of the present invention uses 3-aminopropyltriethoxysilane to treat H-ZSM-5, grafts amino groups, realizes the acid-base bifunction, and is suitable for the synthesis of higher alcohols from high-temperature and high-pressure syngas. Detailed Embodiments To more clearly illustrate the overall concept of the present invention, the following will be described in detail by way of examples.

[0036] In the following description, many specific details are set forth in order to fully understand the present invention. However, the present invention may also be implemented in other ways different from those described herein. Therefore, the scope of protection of the present invention is not limited by the specific embodiments disclosed below.

[0037] Example 1 In one embodiment of the present invention, in the rhodium-based composite catalyst for higher alcohols, Rh is 1 wt%, Fe is 1 wt%, and the acidic carrier ZrO2 is 98 wt%.

[0038] The preparation method of the rhodium-based composite catalyst for higher alcohols includes the following steps: (1) According to the mass percentages in the rhodium-based composite catalyst for higher alcohols, where the mass percentage of the Rh component is 1 wt%, the mass percentage of the Fe component is 1 wt%, and the mass percentage of the acidic carrier ZrO2 is 98 wt%, weigh rhodium chloride, iron nitrate, and ZrO2. Add rhodium chloride to 0.1 M dilute hydrochloric acid to prepare a rhodium chloride solution with a concentration of 1 M, and add iron nitrate to ethanol to prepare an iron nitrate solution with a concentration of 1 M.

[0039] Perform aminosilylation treatment on ZrO2, including the following steps: a1: Wash ZrO2 with 0.1 M dilute nitric acid, and then calcine it at 400 °C for 2 h to stabilize the structure; a2: Add the ZrO2 calcined in step a1 to a solution of 3-aminopropyltriethoxysilane and toluene, where the volume ratio of 3-aminopropyltriethoxysilane to toluene is 1:10, and carry out a reflux reaction at 80 °C for 5 h. Centrifuge to remove the unreacted 3-aminopropyltriethoxysilane and dry it; among them, the mass ratio of 3-aminopropyltriethoxysilane to ZrO2 is 5%.

[0040] a3: Calcine the ZrO2 after the reflux reaction in step a2 in a nitrogen atmosphere at 250 °C to form stable Si-O-Zr bonds, obtaining aminosilylated ZrO2. The average pore diameter of the aminosilylated ZrO2 is 6 nm.

[0041] (2) Impregnate the aminosilylated ZrO2 support with the rhodium chloride solution, and after drying, perform hydrogen reduction treatment at 300 °C for 3 h to obtain ZrO2 loaded with rhodium nanoparticles.

[0042] (3) Impregnate the ZrO2 loaded with rhodium nanoparticles with the iron nitrate solution, and after drying, calcine it at 400 °C for 3 h to obtain Rh-Fe / ZrO2.

[0043] (4) Reduce Rh-Fe / ZrO₂ under a hydrogen atmosphere at 300 °C for 2 h, then pass in a 1% O₂ / N₂ mixed gas to passivate the surface to prevent the oxidation and deactivation of Rh nanoparticles, and finally calcine at 500 °C for 2 h to enhance the mechanical strength, obtaining a rhodium-based composite catalyst for higher alcohols.

[0044] Example 2 In one embodiment of the present invention, in the rhodium-based composite catalyst for higher alcohols, Rh is 8 wt%, Fe is 5 wt%, and the acidic carrier ZrO₂ is 87 wt%.

[0045] The preparation method of the rhodium-based composite catalyst for higher alcohols comprises the following steps: (1) According to the mass percentages in the rhodium-based composite catalyst for higher alcohols, the Rh component is 8 wt%, the Fe component is 5 wt%, and the acidic carrier ZrO₂ is 87 wt%, weigh rhodium nitrate, iron chloride and ZrO₂. Add rhodium nitrate to 0.1 M dilute hydrochloric acid to prepare a rhodium nitrate solution with a concentration of 1 M, and add iron chloride to ethanol to prepare an iron chloride solution with a concentration of 1 M.

[0046] Carry out aminosilylation treatment on ZrO₂, including the following steps: a1: Wash ZrO₂ with 0.1 M dilute nitric acid, and then calcine at 500 °C for 2 h to stabilize the structure; a2: Add the ZrO₂ calcined in step a1 to a solution of 3-aminopropyltriethoxysilane and toluene, where the volume ratio of 3-aminopropyltriethoxysilane to toluene is 1:10, carry out a reflux reaction at 75 °C for 6 h, centrifuge to remove the unreacted 3-aminopropyltriethoxysilane, and carry out drying; among them, the mass ratio of 3-aminopropyltriethoxysilane to ZrO₂ is 10%.

[0047] a3: Calcinate the ZrO₂ after the reflux reaction in step a2 under a nitrogen atmosphere at 350 °C to form stable Si-O-Zr bonds, obtaining aminosilylated ZrO₂. The average pore diameter of the aminosilylated ZrO₂ is 7 nm.

[0048] (2) Impregnate the aminosilylated ZrO₂ support with the rhodium nitrate solution, and after drying, carry out a hydrogen reduction treatment at 250 °C for 3 h to obtain ZrO₂ loaded with rhodium nanoparticles, with Rh particles <5 nm.

[0049] (3) Impregnate the ZrO₂ loaded with rhodium nanoparticles with the iron chloride solution, and after drying, calcine at 350 °C for 3 h to obtain Rh-Fe / ZrO₂.

[0050] (4) Reduce the Rh-Fe / ZrO2 in a hydrogen atmosphere at 350 °C for 2 h, then pass in a 1% O2 / N2 mixed gas to passivate the surface to prevent the Rh nanoparticles from being oxidized and deactivated, and finally calcine at 400 °C for 2 h to enhance the mechanical strength, obtaining a rhodium-based composite catalyst for higher alcohols.

[0051] Example 3 In one embodiment of the present invention, in the rhodium-based composite catalyst for higher alcohols, Rh is 6 wt%, Fe is 5 wt%, and the acidic carrier ZrO2 is 89 wt%.

[0052] The preparation method of the rhodium-based composite catalyst for higher alcohols includes the following steps: (1) According to the mass percentages in the rhodium-based composite catalyst for higher alcohols, the mass percentage of the Rh component is 6 wt%, the mass percentage of the Fe component is 5 wt%, and the mass percentage of the acidic carrier ZrO2 is 89 wt%. Weigh rhodium chloride, iron nitrate, and ZrO2. Add rhodium chloride to 0.1 M dilute hydrochloric acid to prepare a rhodium chloride solution with a concentration of 1 M, and add iron nitrate to ethanol to prepare an iron nitrate solution with a concentration of 1 M.

[0053] Perform an amino-silanization treatment on ZrO2, including the following steps: a1: Wash ZrO2 with 0.1 M dilute nitric acid, and then calcine at 450 °C for 2 h to stabilize the structure; a2: Add the ZrO2 calcined in step a1 to a solution of 3-aminopropyltriethoxysilane and toluene, where the volume ratio of 3-aminopropyltriethoxysilane to toluene is 1:10, and carry out a reflux reaction at 80 °C for 5 h. Centrifuge to remove the unreacted 3-aminopropyltriethoxysilane and perform drying; among them, the mass ratio of 3-aminopropyltriethoxysilane to ZrO2 is 7%.

[0054] a3: Calcine the ZrO2 after the reflux reaction in step a2 in a nitrogen atmosphere at 300 °C to form stable Si-O-Zr bonds, obtaining amino-silanized ZrO2. The average pore diameter of the amino-silanized ZrO2 is 7 nm.

[0055] (2) Immerse the amino-silanized ZrO2 carrier with the rhodium chloride solution, and after drying, perform a hydrogen reduction treatment at 250 °C for 3 h to obtain ZrO2 loaded with rhodium nanoparticles. The Rh particles are <5 nm.

[0056] (3) Immerse the ZrO2 loaded with rhodium nanoparticles with the iron nitrate solution, and after drying, calcine at 400 °C for 3 h to obtain Rh-Fe / ZrO2.

[0057] (4) Reduce Rh-Fe / ZrO2 under a hydrogen atmosphere at 320 °C for 2 h, then pass in a 1% O2 / N2 mixed gas to passivate the surface to prevent the Rh nanoparticles from being oxidized and deactivated, and finally calcine at 500 °C for 2 h to enhance the mechanical strength, obtaining a rhodium-based composite catalyst for higher alcohols.

[0058] Example 4 In an embodiment of the present invention, in the rhodium-based composite catalyst for higher alcohols, Rh is 6 wt%, Fe is 5 wt%, and the acidic support H-ZSM-5 is 89 wt%.

[0059] The preparation method of the rhodium-based composite catalyst for higher alcohols comprises the following steps: (1) According to the mass percentages in the rhodium-based composite catalyst for higher alcohols, the mass percentage of the Rh component is 6 wt%, the mass percentage of the Fe component is 5 wt%, and the mass percentage of the acidic support H-ZSM-5 is 89 wt%, weigh rhodium chloride, iron nitrate and H-ZSM-5. Add rhodium chloride to 0.1 M dilute hydrochloric acid to prepare a rhodium chloride solution with a concentration of 2 M, and add iron nitrate to ethanol to prepare an iron nitrate solution with a concentration of 2 M.

[0060] Perform aminosilylation treatment on H-ZSM-5, including the following steps: b1 Immerse H-ZSM-5 in 0.2 M sodium hydroxide solution and treat it at 70 °C to partially dissolve the silicon-aluminum framework to generate mesopores. After the alkali treatment, the pore diameter of H-ZSM-5 is enlarged to 2 - 5 nm.

[0061] b2 Wash the H-ZSM-5 after the alkali treatment in step b1 with 0.2 M dilute nitric acid, then dry it in sequence and calcine it at 500 °C for 2 h to stabilize the structure and remove the adsorbed water, obtaining activated H-ZSM-5.

[0062] b3 Immerse the activated H-ZSM-5 in a solution of 3-aminopropyltriethoxysilane and toluene and perform ultrasonic treatment for 30 min to promote diffusion. Among them, the volume ratio of 3-aminopropyltriethoxysilane to toluene is 1:20, and carry out a reflux reaction at 80 °C for 10 h to fully graft the silane. Then, perform centrifugal separation, washing and drying in sequence, and heat-treat it under a nitrogen atmosphere at 150 °C for 2 h to obtain aminosilylated H-ZSM-5.

[0063] (2) Impregnate the aminosilylated H-ZSM-5 with the rhodium chloride solution, and after drying, perform hydrogen reduction treatment at 250 °C for 3 h to obtain H-ZSM-5 loaded with rhodium nanoparticles. The Rh particles are <5 nm.

[0064] (3) Impregnate the H-ZSM-5 loaded with rhodium nanoparticles with the iron nitrate solution, and after drying, calcine it at 400 °C for 3 h to obtain Rh-Fe / H-ZSM-5.

[0065] (4) The Rh-Fe / H-ZSM-5 was reduced at 320 °C for 2 h in a hydrogen atmosphere, and then a 1% O2 / N2 mixed gas was introduced to passivate the surface to prevent the oxidation and deactivation of Rh nanoparticles. Finally, it was calcined at 500 °C for 2 h to enhance the mechanical strength, obtaining a rhodium-based composite catalyst for higher alcohols.

[0066] Example 5 In one embodiment of the present invention, in the rhodium-based composite catalyst for higher alcohols, Rh is 6 wt%, Fe is 5 wt%, K is 2 wt%, and the acidic support H-ZSM-5 is 87 wt%.

[0067] The preparation method of the rhodium-based composite catalyst for higher alcohols includes the following steps: (1) According to the mass percentages in the rhodium-based composite catalyst for higher alcohols, Rh is 6 wt%, Fe is 5 wt%, K is 2 wt%, and the acidic support H-ZSM-5 is 87 wt%, weigh rhodium chloride, iron nitrate, potassium nitrate, and H-ZSM-5. Add rhodium chloride to 0.1 M dilute hydrochloric acid to prepare a rhodium chloride solution with a concentration of 2 M, and add iron nitrate and potassium nitrate to deionized water to prepare iron nitrate solution and potassium nitrate solution with a concentration of 2 M.

[0068] The H-ZSM-5 is subjected to aminosilylation treatment, including the following steps: b1 Immerse the H-ZSM-5 in 0.2 M sodium hydroxide solution and treat it at 70 °C to partially dissolve the silicon-aluminum framework to generate mesopores. After the alkali treatment, the pore diameter of H-ZSM-5 is expanded to 2 - 5 nm.

[0069] b2 Acid-wash the H-ZSM-5 treated in step b1 with 0.2 M dilute nitric acid, then dry it successively and calcine it at 500 °C for 2 h to stabilize the structure and remove adsorbed water, obtaining activated H-ZSM-5.

[0070] b3 Immerse the activated H-ZSM-5 in a solution of 3-aminopropyltriethoxysilane and toluene and ultrasonically treat it for 30 min to promote diffusion. Among them, the volume ratio of 3-aminopropyltriethoxysilane to toluene is 1:20, and carry out a reflux reaction at 80 °C for 10 h to fully graft the silane. Then, centrifuge and separate, wash and dry, and heat-treat it at 150 °C in a nitrogen atmosphere for 2 h to obtain aminosilylated H-ZSM-5.

[0071] (2) Mix the rhodium chloride solution and iron nitrate, and dropwise add the aminosilylated H-ZSM-5, ultrasonically assist for 30 minutes to ensure uniform penetration, stand at room temperature for 15 h, and dry at 90 °C for 12 h to obtain Rh-Fe / H-ZSM-5.

[0072] (3) Impregnate the Rh-Fe / H-ZSM-5 with potassium nitrate solution, dry it, and then calcine it at 400 °C for 4 h to obtain Rh-Fe-K / H-ZSM-5.

[0073] (4) Reduce the Rh-Fe-K / H-ZSM-5 in a hydrogen atmosphere at 320 °C for 2 h, then pass a 1% O2 / N2 mixed gas to passivate the surface to prevent the oxidation and deactivation of Rh nanoparticles, and finally calcine it at 500 °C for 2 h to enhance the mechanical strength to obtain a rhodium-based composite catalyst for higher alcohols.

[0074] Example 6 Based on Example 5, the main difference is that in the rhodium-based composite catalyst for higher alcohols, Rh is 6 wt%, Mn is 5 wt%, K is 2 wt%, and the acidic carrier H-ZSM-5 is 87 wt%.

[0075] In the preparation method, ferric nitrate is replaced with manganese nitrate, and other steps are the same as those in Example 5.

[0076] Example 7 Based on Example 5, the main difference is that the acidic carrier H-ZSM-5 is replaced with the acidic carrier ZrO2, and in the rhodium-based composite catalyst for higher alcohols, Rh is 6 wt%, Fe is 5 wt%, K is 2 wt%, and the acidic carrier ZrO2 is 87 wt%. The step of aminopropylsilane treatment of ZrO2 is the same as that in Example 3, and other steps are the same as those in Example 5.

[0077] Example 8 Based on Example 6, the main difference is that in the rhodium-based composite catalyst for higher alcohols, Rh is 6 wt%, Mn is 5 wt%, Cs is 2 wt%, and the acidic carrier H-ZSM-5 is 87 wt%. In the preparation method, potassium nitrate is replaced with cesium nitrate, and other steps are the same as those in Example 6.

[0078] Example 9 Based on Example 1, the main difference is that N-aminoethyl-3-aminopropylmethyldimethoxysilane is used for aminopropylsilane treatment of ZrO2. Other steps are the same as those in Example 1.

[0079] Example 10 Based on Example 1, the main difference is that the second active metal is 12 wt%, and other steps are the same as those in Example 1.

[0080] Example 11 Based on Example 1, the main difference is that the first active metal is 0.2 wt%.

[0081] Comparative Example 1 Based on Example 1, the main difference is that the acidic carrier is not subjected to aminopropylsilane treatment.

[0082] Comparative Example 2 On the basis of Example 1, the main difference is that the second active metal is not added.

[0083] Test Example The high-carbon alcohol prepared from the above-mentioned examples and comparative examples with the rhodium-based composite catalyst was applied to the reaction of synthesizing high-carbon alcohol from syngas. Before the direct synthesis of high-carbon alcohol from syngas, the catalyst was first subjected to reduction pretreatment. The high-carbon alcohol prepared from the examples and comparative examples with the rhodium-based composite catalyst was loaded into a fixed-bed reactor for reduction pretreatment: the reduction temperature was 400 °C, the reduction gas was a mixture of hydrogen and CO, and the space velocity was 8000 h -1 , and the reduction treatment time was 6 h.

[0084] When the syngas reacts, the molar ratio of H2 to CO in the syngas is 2, and the reaction space velocity is 4000 h -1 , the reaction temperature is 300 °C, the reaction pressure is 6 MPa. After the reaction, gas chromatography is used to analyze the types and contents of each component contained in the product. And the conversion rate and selectivity of this reaction are calculated accordingly. The results are shown in Table 1 for reference.

[0085] Table 1

[0086] As shown in Table 1 for reference, the rhodium-based composite catalyst for high-carbon alcohol of the present invention can be used for synthesizing high-carbon alcohol from syngas. When the syngas reaction is carried out at a relatively high temperature (300 °C) and pressure, the CO conversion rate is not less than 25%, and the selectivity of C6+ alcohol is not less than 25%. The rhodium-based composite catalyst for high-carbon alcohol prepared in the present invention has high (C6+) selectivity.

[0087] Stability test: When the molar ratio of H2 to CO in the syngas is 2, the reaction space velocity is 4000 h -1 , the reaction temperature is 300 °C, the reaction pressure is 6 MPa, and continuous operation is carried out for 300 h. The rhodium-based composite catalyst for high-carbon alcohol prepared from the above-mentioned examples was subjected to a stability test. After 300 h, the volatility change of the CO conversion rate was about 6%, and the volatility change of the C6+ alcohol selectivity was about 4%. Compared with the existing Rh-based catalyst (which will sinter and deactivate after running for 300 h), it is proved that the rhodium-based composite catalyst for high-carbon alcohol prepared in this application has improved stability and has good anti-sintering and anti-poisoning abilities.

[0088] The above are only the embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention can have various changes and modifications. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included within the scope of the claims of the present invention.

Claims

1. A rhodium-based composite catalyst for higher alcohols, characterized in that, The rhodium-based composite catalyst for higher alcohols comprises a first active metal, a second active metal, and an acidic support treated by aminosilylation. The first active metal is Rh, the second active metal is one or more of Fe, Mn, K, or Cs, and the acidic support is ZrO2 or H-ZSM-5.

2. The rhodium-based composite catalyst for higher alcohols according to claim 1, characterized in that, By mass fraction, the first active metal is 0.5 wt% - 10 wt%, the second active metal is 0.5 wt% - 8 wt%, and the acidic support is 85 wt% - 98 wt%.

3. The rhodium-based composite catalyst for higher alcohols according to claim 1, characterized in that, The aminosilylation treatment of ZrO2 includes the following steps: a1: Wash ZrO2 with acid, and then calcine it at 400 - 550 °C. a2: Add the ZrO2 calcined in step a1 into a solution of 3-aminopropyltriethoxysilane and toluene, and carry out a reflux reaction at 75 - 85 °C. a3: Calcine the ZrO2 after the reflux reaction in step a2 in an inert atmosphere at 250 - 350 °C to obtain aminosilylated ZrO2.

4. The rhodium composite catalyst for higher alcohols according to claim 3, wherein The pore diameter of the aminosilylated ZrO2 is 5 - 10 nm; and / or the mass ratio of 3-aminopropyltriethoxysilane to ZrO2 is 5% - 10%.

5. The rhodium-based composite catalyst for higher alcohols according to claim 1, wherein, The aminosilylation treatment of H-ZSM-5 includes the following steps: b1: Immerse H-ZSM-5 in an alkali solution and treat it at 70 - 80 °C. b2: Acid-wash the H-ZSM-5 after the alkali treatment in step b1, and then dry and calcine it in sequence to obtain activated H-ZSM-5. b3: Immerse the activated H-ZSM-5 in a solution of 3-aminopropyltriethoxysilane and toluene, carry out a reflux reaction at 75 - 85 °C, and then dry and heat-treat it in an inert atmosphere in sequence to obtain aminosilylated H-ZSM-5.

6. The rhodium-based composite catalyst for higher alcohols according to claim 5, characterized in that, The pore diameter of the H-ZSM-5 after the alkali treatment in step b1 is 2 - 5 nm; and / or the calcination temperature in step b2 is 450 - 550 °C; and / or the heat-treatment temperature in an inert atmosphere in step b3 is 140 - 160 °C; and / or the mass ratio of 3-aminopropyltriethoxysilane to H-ZSM-5 is 5% - 15%.

7. A method for preparing a rhodium-based composite catalyst for higher alcohols according to any one of claims 1-6, characterized in that, The preparation method includes the following steps: (1) Weigh the corresponding soluble salts and acidic support respectively according to the proportion of the first active metal and the second active metal in the total mass of the catalyst. Mix the soluble salt of the first active metal with a first solvent to obtain a first solution; mix the soluble salt of the second active metal with a second solvent to obtain a second solution. (2) Impregnate the support with the first solution, dry it, and then carry out a reduction treatment at a certain temperature to obtain an acidic support loaded with the first active metal. (3) Impregnate the acidic support loaded with the first active metal with the second solution, dry it, and then carry out a calcination treatment to obtain an acidic support loaded with the second active metal. (4) Carry out a reduction treatment on the acidic support loaded with the second active metal at a certain temperature, and then carry out passivation and calcination and qualitative treatment in sequence to obtain the rhodium-based composite catalyst for higher alcohols.

8. The preparation method according to claim 7, characterized in that, The soluble salt of the first active metal is one of rhodium chloride or rhodium nitrate; and / or the soluble salt of the second active metal is one or more of ferric nitrate, ferrous sulfate, manganese nitrate, manganese sulfate, potassium nitrate, cesium nitrate, cesium chloride.

9. The preparation method according to claim 7, characterized in that, In step (2), the reduction treatment temperature is 250 - 300 °C; and / or in step (3), the calcination temperature is 350 - 450 °C; and / or in step (4), the reduction treatment temperature is 300 - 350 °C, and the calcination and qualitative treatment temperature is 400 - 550 °C.

10. Use of the rhodium-based composite catalyst for higher alcohols according to any one of claims 1 - 6 in the direct preparation of higher alcohols from syngas.

Citation Information

Patent Citations

  • Alcohol synthesis from co or co2

    CN101341110A

  • Polyvinylpyrrolidone (PVP)-modified rhodium-based catalyst and preparation method thereof and application

    CN107029715A

  • Preparation method of catalyst for ethanol synthesis and catalyst obtained thereby and application of catalyst

    CN108238846A

  • Preparation of nano-catalyst for repairing organic pollution of groundwater and use method thereof

    CN113797953A

  • Catalyst for ethanol synthesis, preparation method therefor and use thereof

    WO2018121324A1